RISK FACTORS OF OBESITY IN YOUNG ADULTS - Lubis, Mestika Natalia; Debora, Novita Stefani; Situmorang, Windy Putriani; Siregar, Deborah; Harefa, Lenny (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Obesity is a developing global public health issue. Obesity is a significant risk factor for a variety of diseases, increasing morbidity and mortality from cardiovascular disease and Diabetes Mellitus. Since 1975, global obesity has nearly tripled, and Jakarta has the second-highest obesity rate in Indonesia. COVID-19 also contributed to this situation, as many young adults work from home. COVID-19 has an impact, such as an increase in the frequency of unhealthy eating and frequency of sitting, a decrease in physical activity, or irregular exercise, which can lead to obesity. This study aims to investigate the lifestyle risk factors associated with obesity in young adults in Jakarta. A cross-sectional design was conducted with convenience sampling of 384 respondents aged 26-35. Data was collected using an online questionnaire. Descriptive and statistical analysis was performed using chi-square. The finding revealed a significant relationship between physical activity, sedentary lifestyle, and genetics with obesity in young adults (p-value 0.004; 0.035; 0.001). Conclusion: Young adults can adopt a healthy lifestyle by increasing regular physical activity for at least 30 minutes daily and changing their sedentary lifestyle.